Pengaruh Ekstrak Etanol pada Tomat (Solanum lycopersicum L.) pada Staphylococcus epidermidis secara in Vitro - Pauzan Pauzan; Musparlin Halid; Wulan Ratia Ratulangi (Jurnal Ilmiah Kesehatan Sandi Husada, 2023)
Tomato is one of the plants that contain lycopene as an antibacterial. Acne is an infectious disease caused by Staphylococcus epidermidis. Antibiotic treatment starts to become resistant so that plants can be used as alternative treatments. The study aimed to determine the effectiveness of the ethanolic extract of tomato (Solanum lycopersicum L) against the growth of Staphylococcus epidermidis bacteria in vitro. This type of research is experimental. Extraction was carried out by maceration method with 96% ethanol as solvent. Lycopene extract with concentrations of 20%, 40%, 60%, 80%, and 100%. Testing with the paper disk method with five repetitions. Aquadest as a negative control, and tetracycline as a positive control. The results showed that the diameter of the inhibition zone formed in the positive control was 40.36 mm (potent inhibition). Inhibition zones at concentrations of 100%, 80%, 60%, 40%, and 20% had solid inhibitory power. The results of statistical tests showed that the ethanolic extract of tomato (Solanum lycopersycom L) had antibacterial effectiveness against the growth of Staphylococcus epidermidis bacteria that causes acne in vitro. The post hoc test shows a significant effect between a T1 concentration of 100% with negative control and positive control